STRATEGI PEMASARAN ONDE-ONDE UBI UNGU “AL-KARIM” DI DUSUN TUNGU DESA KAYANGAN KECAMATAN DIWEK KABUPATEN JOMBANG - Fahmi, Mijar Alif; Pudjiastuti, Agnes Quartina; Rofiatin, Umi Rofiatin (BUANA SAINS, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are economic pillars that often face marketing challenges. One of them is the Al-Karim purple sweet potato onde-onde business, which experiences obstacles in implementing an effective marketing mix. This study aims to analyze the implementation of the marketing mix and formulate an appropriate development strategy for the Al-Karim business. The research method employed is a quantitative descriptive approach, utilizing IFE-EFE Matrix analysis, IE Matrix, SWOT, and QSPM. The results showed that the IE Matrix analysis placed the Al-Karim business in cell V (Hold and Maintain strategy) with an IFE score of 2.250 and an EFE score of 2.382. Based on this position, the SWOT Matrix produced eight alternative strategies. Furthermore, the QSPM analysis determined three priority strategies, namely: (1) improving and maintaining product quality (TAS value 4.50); (2) intensifying promotions by utilizing technology (TAS value 4.38); and (3) expanding the marketing distribution area (TAS value 4.36).